2011
DOI: 10.1007/s00421-011-2260-1
|View full text |Cite
|
Sign up to set email alerts
|

Climbing-specific finger flexor performance and forearm muscle oxygenation in elite male and female sport climbers

Abstract: Climbing performance relies to a great extent on the performance of the finger flexor muscles. Only a few studies investigated this performance in top class climbers and only one study compared gender-specific differences. This study investigated the climbing-specific finger flexor strength and endurance and related muscular oxygenation in 12 elite female and male climbers and 12 non-climbers. After the assessment of maximum voluntary finger flexor contraction (MVC), two isometric finger flexor endurance tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
129
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(142 citation statements)
references
References 38 publications
10
129
2
1
Order By: Relevance
“…The many years of climbing practice, therefore, seem to have increased the finger flexors capacities by almost 40 %. This result was obviously expected given the numerous studies which demonstrated significant higher performances of climbers when grasping fingertip holds (Watts and Drobish 1998;Mermier et al 1997;Cutts and Bollen 1985;Grant et al 2003;Philippe et al 2012). Nevertheless, this study brought new information by quantifying this improvement at the muscle level.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The many years of climbing practice, therefore, seem to have increased the finger flexors capacities by almost 40 %. This result was obviously expected given the numerous studies which demonstrated significant higher performances of climbers when grasping fingertip holds (Watts and Drobish 1998;Mermier et al 1997;Cutts and Bollen 1985;Grant et al 2003;Philippe et al 2012). Nevertheless, this study brought new information by quantifying this improvement at the muscle level.…”
Section: Discussionsupporting
confidence: 59%
“…However, additional subjects and one non-climber female sample should be tested to confirm this trend. One interesting point is that normalizing the moment-generating capacities with the body mass of each individual, as it is generally done to highlight the performance of climbers (Philippe et al 2012), does not change the results significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with previous research (Philippe et al 2011;Schweizer and Hudek 2011) the FDP was assessed as it has been deemed to be the most important finger flexor for rock climbing performance. Although previous research has shown that different sections of a muscle have different deoxygenation responses (Koga et al 2007), the authors of the current study have made every attempt to ensure consistent probe placement between participants.…”
Section: Methodsmentioning
confidence: 78%
“…Rock climbing performance has been suggested to be dependent on the endurance characteristics of the forearm skeletal muscles (Watts et al 1993), particularly the flexor digitorum profundus (FDP) as it bends the distal joint of fingers 2, 3, 4 and 5 (used in the open crimp position) (Philippe et al 2011). In turn, the endurance of the FDP would be expected to be dependent on the ability to (i) deliver and (ii) use oxygen (Fryer et al 2015b).…”
Section: Introductionmentioning
confidence: 99%